Sāk vitt ok vītt of verǫld hverja (acousmonium version) - Koutsomichalis, Marinos (My University, 2026)
'Sāk vitt ok vītt of verǫld hverja' artistic project performed live employing a 28-speakers acousmonium. https://evenemang2.malmo.se/en/item/acousmatic-stories/bsikq5ckaevhlutvssyys3eqrtymfwok